Interpretation of the 2024 BASHH & RCOG UK guideline on HSV management in pregnancy: key recommendations and comparison with Chinese clinical practice - FERREIRA Esmeraldito; CHEN Zhaoqi; KE Wujian (Pifu-xingbing zhenliaoxue zazhi)
Herpes simplex virus (HSV) types 1 and 2 pose significant health risks during pregnancy, impacting both maternal and neonatal outcomes. The 2024 joint guideline from the British Association for Sexual Health and HIV (BASHH) and the Royal College of Obstetricians and Gynaecologists (RCOG) in the United Kingdom introduces updated recommendations to reduce maternal-to-neonatal transmission. Key recommendations include initiating antiviral therapy earlier—at 32 weeks for standard pregnancies or as early as 22 weeks in high-risk cases—to minimize viral shedding. The guideline emphasizes polymerase chain reaction (PCR) testing for accurate diagnosis and advocates a multidisciplinary team (MDT) approach, involving genitourinary medicine (GUM) specialists, obstetricians, and neonatologists for delivery planning and neonatal care. However, the Chinese guidelines offer greater flexibility in the timing of antiviral treatment, tailored to regional resources and specific circumstances. PCR testing is also recommended, particularly in urban hospitals and tertiary care settings. The UK's MDT model aligns with China's integrative healthcare approach, presenting opportunities for mutual learning and collaboration. This comparative analysis highlights areas for cross-adaptation in clinical practices, with potential to enhance maternal and neonatal health outcomes globally.